Relationship between Anxiety and Epigastric Pain and Postprandial Distress Syndrome in Medical Students of Halu Oleo University Kendari - Rizqi Rayyan Shaffana; Pranita Aritrina S; Edy Husnul Mujahid (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
Background: Anxiety is a psychological condition in the form of excessive anxiety that is often experienced by medical students due to the influence of high academic loads being one of the factors causing anxiety disorders involving digestive disorders, triggering the occurrence of Epigastric Pain Syndrome and Postprandial Distress Syndrome. Purpose(s): This study aims to determine whether there is a relationship between anxiety and Epigastric Pain Syndrome and Postprandial Distress Syndrome in students of the Faculty of Medicine, Halu Oleo University. Methods: This study was an observational analytic study using a cross-sectional approach method of Halu Oleo University Faculty of Medicine students from the Class of 2021, 2022, and 2023, obtained a total sample of 190 samples taken using proportional stratified random sampling technique. Data were collected using the Hamilton Anxiety Rating Scale (HARS) and R4-FDDQ (Rome IV Functional Dyspepsia Diagnostic Questionnaire) questionnaires using the Chi Square test. Results: In this study showed a significant relationship between anxiety levels and the incidence of Epigastric Pain Syndrome (EPS) p-value = <0.001 and there was a significant relationship anxiety levels and the incidence of Postprandial Distress Syndrome (PDS) p-value = <0.001 in students of the Faculty of Medicine, Halu Oleo University. Conclusion: There is a significant relationship between anxiety and Epigastric Pain Syndrome and there is a significant relationship between anxiety and Postprandial Distress Syndrome in students of the Faculty of Medicine, Halu Oleo University Kendari